2019
DOI: 10.1371/journal.pone.0221090
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal effect of aconitine on the rice brown planthoppers

Abstract: The brown planthopper, Nilaparvata lugens (Stål), severely damages rice production and develops high level resistance to several classes of insecticides. To find potential insecticidal resources is always important. As an environmentally friendly compound, aconitine exhibits potential pesticide features. In the present study, the pesticide and knockdown effects of aconitine were first tested on the brown planthopper. The results showed that the knockdown rates for an aconitine concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The results revealed that the knockdown rate for an AC concentration of 200 ppm was 83.6%, and the insecticidal LD50 was 22.68 ng/pest. Furthermore, AC may be neurotoxic to the brown planthopper, and the conscious nymphs are resistant to drug neurotoxicity by upregulating CYP3A4, UGT, and GABA receptor mutations [68]. The gut microbiota played an important role in pheromone production, pesticide degradation, vitamin synthesis, and pathogen prevention in the host animal.…”
Section: Biological Activitymentioning
confidence: 99%
“…The results revealed that the knockdown rate for an AC concentration of 200 ppm was 83.6%, and the insecticidal LD50 was 22.68 ng/pest. Furthermore, AC may be neurotoxic to the brown planthopper, and the conscious nymphs are resistant to drug neurotoxicity by upregulating CYP3A4, UGT, and GABA receptor mutations [68]. The gut microbiota played an important role in pheromone production, pesticide degradation, vitamin synthesis, and pathogen prevention in the host animal.…”
Section: Biological Activitymentioning
confidence: 99%
“…The brown planthopper (BPH), Nilaparvata lugens (St å l) (Hemiptera: Delphacidae), is one of the economically important insect pests identified in this crop, having an international significance ( Normile, 2008 ; Heong & Hardy, 2009 ). This phloem sap feeder transmits rice ragged stunt virus (RRSV) and rice grassy stunt virus (RGSV), and holds the ability to cause more than 60% economic yield loss under favourable environmental conditions throughout Asia ( Kumar, Maurya & Tiwari, 2012 ; Wei et al, 2019 ). Several chemical insecticides are registered to control rice BPH, but the unscientific and injudicious application of those products breaks the natural pest defender ratio in the field ( Sarao & Mangat, 2014 ; Roy & Chakraborty, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of over twenty insects species recognized as economically important pests of this crop, the brown planthopper (BPH), Nilaparvata lugens (Stål) (Homoptera: Delphacidae) is one of them (Normile 2008;Heong and Hardy 2009). This phloem sap feeder is known to be one of the most destructive and notorious pests of rice throughout Asia and hold the ability to create as high as 60% yield loss under epidemic conditions (Kumar et al 2012;Wei et al 2019). Host-plant resistance to insect injury occurs in plants that use strategies to recover, tolerate or avoid from the attack of pest (Smith 2005); thus, plant characteristics that have negative influences on insect-pest biology, reproduction and development could be used in the screening of plants resistant to insect (Rekha and Singh 2001).…”
Section: Introductionmentioning
confidence: 99%